New Evidence on the Evolution of the COVID-19 Pandemic: Literature Review - Leyla S. Namazova-Baranova; Nilab Sadeqi; Kamilla E. Efendieva (Педиатрическая фармакология)
This review presents new publicly available data on the evolution of COVID-19 pandemic caused by SARS-CoV-2, as well as on the Delta variant. The article also covers the issues of terminology and classification of already identified virus variants, vaccination efficacy, and the use monoclonal antibodies for SARS-CoV-2 virus and new Delta variant management. The authors of all analyzed publications consider the Delta variant as the most concerning in the present situation. It is noted, there is data (according to some publications) indicating its higher transmissibility, hospitalization risk, likely more severe disease course, low efficacy of vaccines after partial vaccination (e.g. one dose of vaccine). The article also considers issues related to children returning to sport activities after COVID-19.